Collateral Damage: September 11th and the Performance of the Faith-Based and Community Initiative - John CHANDLER (Cahiers du MIMMOC)
One of the major policy innovations implemented by newly elected George W. Bush was his Faith-Based and Community Initiative. The objective of the Initiative was to create a “level playing field” where faith-based organizations could compete with secular organizations for government funding of social aid programs.This analysis advances that the timing of 9/11 and its relation to the developments within American government conspired to create substantial collateral damage concerning the effectiveness of the policy. While acknowledging that 9/11 did not instigate debate concerning the policy, the study evaluates how it nevertheless was in a number of ways a catalyst in: 1) the intensification of conflict concerning such policy and 2) the Bush administration’s failure to effectively apply it.In order to show how 9/11 had an influence on the development and execution of the policy, a very short but necessary description of the background of the program leading up to the event constitutes the first part of the analysis. Subsequently, a second part evaluates how 9/11 had an impact on faith-based policy and its performance. The study highlights one of the most important inner-circle players on Bush’s faith-based policy team at the time of the attacks, John Dilulio Jr., the Director of the White House Office of Faith-Based and Community Initiatives. I concentrate particularly on Dilulio as his case provides a unique and efficient vehicle for illustrating both the chain of events leading up to 9/11 as well as the collateral damage to faith-based policy.